Actualización diagnóstica y terapéutica de la colecistitis aguda. - León Iza, Karen Lisbeth (2023)
Acute cholecystitis has a global prevalence that places it among the leading causes of hospitalization for abdominal pain. It is a pathology with a varied clinical presentation, so making an early diagnosis and treatment is essential. The diagnosis or inadequate management of acute cholecystitis can lead to severe complications. The objective of this review is mainly to develop a diagnostic update and therapy for acute cholecystitis. For this, a non-experimental systematic review of the literature related to the diagnostic and therapeutic update of acute cholecystitis was carried out, including updated information with a maximum publication time of 5 years, reducing any bias derived from previous research. The main result was that the diagnostic and therapeutic update of acute cholecystitis is essential in medical practice seeking better clinical outcomes and good quality of life for patients, based fundamentally on the Tokyo guidelines 18 and their criteria focused on the manifestations, clinical, laboratory, and imaging findings, which serve to guide diagnosis and treatment.